Teori Pemerolehan Bahasa Pertama dan Kaitannya dengan Kemampuan Awal Peserta Didik - A. Hilwa Syauqy Mazidah; Alfa Sabila Ainurrahma; Rizqi Maulana; M. Yunus Abu Bakar (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2025)
First Language Acquisition is a crucial process influenced by various language learning theories. This research aims to comprehensively analyze the application of the main L1 theories, such as Behaviorism, Nativism, and Interactionism, and to thoroughly examine the concept, utility, and identification techniques of students’ prior knowledge within the context of child language acquisition. Employing a critical analytica l literature review method, the findings indicate that L1 Acquisition is not solely explained by one theory but results from the interaction between innate endowment (LAD) and environmental input. A key finding highlights that the identification of prior knowledge, encompassing cognitive, linguistic, and social aspects, is highly functional as a basis for determining appropriate scaffolding and providing comprehensible language input. The most relevant detection techniques involve direct observation and analysis of children’s spontaneous speech.It is concluded that a holistic understanding of L1 theories and the early identification of prior knowledge is essential for educators and parents. This finding has implications for formulating personalized language development strategies, thereby optimizing children’s language potential from an early age.